2010
DOI: 10.1161/circulationaha.109.889071
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Creation of an Atrial Septal Defect by Histotripsy in a Canine Model

Abstract: Background-The primary objective of this study was to develop an image-guided, noninvasive procedure to create or enlarge an atrial septal defect for the treatment of neonates with hypoplastic left heart syndrome and an intact or restrictive atrial septum. Histotripsy is an innovative ultrasonic technique that produces nonthermal, mechanical tissue fractionation through the use of high-intensity ultrasound pulses. This article reports the pilot in vivo study to create an atrial septal defect through the use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
84
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(85 citation statements)
references
References 33 publications
1
84
0
Order By: Relevance
“…Questions concerning the most effective technique for opening the atrial septum in utero, including balloon atrial septoplasty versus stent placement, in addition to the optimal timing to perform the procedure to mitigate against the development of pulmonary vasculopathy, remain unanswered. [483][484][485][486] However, given the significant mortality and morbidity of HLHS with a restrictive or intact atrial septum, fetal intervention may be reasonable to perform in this disease, not only to stabilize the patient in the immediate postnatal period but also to potentially prevent or reverse the damage to the lungs and vasculature.…”
Section: Hlhs With Restrictive or Intact Atrial Septummentioning
confidence: 99%
“…Questions concerning the most effective technique for opening the atrial septum in utero, including balloon atrial septoplasty versus stent placement, in addition to the optimal timing to perform the procedure to mitigate against the development of pulmonary vasculopathy, remain unanswered. [483][484][485][486] However, given the significant mortality and morbidity of HLHS with a restrictive or intact atrial septum, fetal intervention may be reasonable to perform in this disease, not only to stabilize the patient in the immediate postnatal period but also to potentially prevent or reverse the damage to the lungs and vasculature.…”
Section: Hlhs With Restrictive or Intact Atrial Septummentioning
confidence: 99%
“…Promising animal studies have shown the potential of histotrispy, a novel ultrasonic technique that produces non-thermal, mechanical tissue fractionation through the use of high-intensity ultrasound pulses, in the non-invasive creation of atrial and ventricular septal defects [21,22]. Perhaps a measured delivery of such a therapy can result in the treatment of local or even global myocardial hypertrophy.…”
Section: Alternative Techniquesmentioning
confidence: 99%
“…As such, creating an atrial septal communication after birth is probably too late to mitigate the pulmonary pathological process, and an alternative such as noninvasive creation of atrial septal defect by histotripsy is still not clinically available yet. 23 Paucity of an animal model of HLHS-IAS currently prevents us from conducting an experiment that includes perforation of an intact septum with the subsequent placement of a stent. In the sheep model at the gestational age we used, the large size of the fetal FO with the little area of septum available for stent placement outside the FO renders intraseptal positioning of an 8-mm stent impossible.…”
Section: Downloaded From Stenting the Foramen Ovale In Fetal Sheepmentioning
confidence: 99%